Spectroscopic investigations of bis(sulfoximine) copper(II) complexes and their relevance in asymmetric catalysis. - Bolm, C; Martin, M; Gescheidt, G; Palivan, C; Neshchadin, D; Bertagnolli, H; Feth, M; Schweiger, A; Mitrikas, G; Harmer, J (2003)
The structure of Cu(II) complex 3 formed within the course of a stereoselective Diels-Alder reaction was investigated by EXAFS, CW-EPR at X- and W-band, HYSCORE, pulsed ENDOR, and UV-vis spectroscopy. The experimental techniques indicate that the chiral bis(sulfoximine) ligand (S,S)-1 and the dienophile form a tetragonally distorted complex in CH(2)Cl(2). The ligand binds to the Cu(II) center via the imine nitrogens, whereas the dienophile interacts via the carbonyl oxygen atoms. The additional sites of the first coordination sphere are occupied by counterions and, presumably, solvent molecules. At the axial position, a triflate anion binds via an oxygen atom.